Ovine abortion — causes and diagnosis. (2nd January 2019) - Dun, Kathryn
Abstract : Annually it is estimated that 2–3% of the national flock will produce premature or stillborn lambs. However, infectious causes can also result in much higher abortion storms in individual flocks. An accurate diagnosis of infectious causes is important to manage the current abortion outbreak, safeguard farm workers from zoonotic infections and to allow control plans to be put into place for future years. This article will cover the diagnosis of ovine abortion and some of the main infectious causes in the UK flock.